ISPD guidelines for peritoneal dialysis in acute kidney injury: 2020 update (adults). Issue 1 (January 2021) - Cullis, Brett; Al-Hwiesh, Abdullah; Kilonzo, Kajiru; McCulloch, Mignon; Niang, Abdou; Nourse, Peter; Parapiboon, Watanyu; Ponce, Daniela; Finkelstein, Fredric O
Summary statements: (1) Peritoneal dialysis (PD) should be considered a suitable modality for treatment of acute kidney injury (AKI) in all settings(1B) . Guideline 2: Access and fluid delivery for acute PD in adults: (2.1) Flexible peritoneal catheters should be used where resources and expertise exist(1B) (optimal) . (2.2) Rigid catheters and improvised catheters using nasogastric tubes and other cavity drainage catheters may be used in resource-poor environments where they may still be life-saving(1C) (minimum standard) . (2.3) We recommend catheters should be tunnelled to reduce peritonitis and peri-catheter leak(practice point) . (2.4) We recommend that the method of catheter implantation should be based on patient factors and locally available skills(1C) . (2.5) PD catheter implantation by appropriately trained nephrologists in patients without contraindications is safe and functional results equate to those inserted surgically(1B) . (2.6) Nephrologists should receive training and be permitted to insert PD catheters to ensure timely dialysis in the emergency setting(practice point). (2.7) We recommend, when available, percutaneous catheter insertion by a nephrologist should include assessment with ultrasonography(2C) . (2.8) Insertion of PD catheter should take place under complete aseptic conditions using sterile technique(practice point) . (2.9) We recommend the use of prophylactic antibiotics prior to PD catheter implantation(1B) . (2.10) A closed delivery system with a Y connection should be used(1A) (optimal) . In resource poor areas, spiking of bags and makeshift connections may be necessary and can be considered(minimum standard) . (2.11) The use of automated or manual PD exchanges are acceptable and this will be dependent on local availability and practices(practice point) . Guideline 3: Peritoneal dialysis solutions for acute PD: (3.1) In patients who are critically ill, especially those with significant liver dysfunction and marked elevation of lactate levels, bicarbonate containing solutions should be used (1B) (optimal) . Where these solutions are not available, the use of lactate containing solutions is an alternative(practice point) (minimum standard) . (3.2) Commercially prepared solutions should be used(optimal) . However, where resources do not permit this, then locally prepared fluids may be life-saving and with careful observation of sterile preparation procedure, peritonitis rates are not increased(1C) (minimum standard) . (3.3) Once potassium levels in the serum fall below 4 mmol/L, potassium should be added to dialysate (using strict sterile technique to prevent infection) or alternatively oral or intravenous potassium should be given to maintain potassium levels at 4 mmol/L or above(1C) . (3.4) Potassium levels should be measured daily(optimal) . Where these facilities do not exist, we recommend that after 24 h of successful dialysis, one consider adding potassium chloride to achieve a concentration of 4 mmol/L in the dialysate(minimum standard) (practice point). Guideline 4: Prescribing and achieving adequate clearance in acute PD: (4.1) Targeting a weekly K t / V urea of 3.5 provides outcomes comparable to that of daily HD in critically ill patients; targeting higher doses does not improve outcomes(1B) . This dose may not be necessary for most patients with AKI and targeting a weekly K t / V of 2.2 has been shown to be equivalent to higher doses(1B) . Tidal automated PD (APD) using 25 L with 70% tidal volume per 24 h shows equivalent survival to continuous venovenous haemodiafiltration with an effluent dose of 23 mL/kg/h(1C) . (4.2) Cycle times should be dictated by the clinical circumstances. Short cycle times (1–2 h) are likely to more rapidly correct uraemia, hyperkalaemia, fluid overload and/or metabolic acidosis; however, they may be increased to 4–6 hourly once the above are controlled to reduce costs and facilitate clearance of larger sized solutes(2C) . (4.3) The concentration of dextrose should be increased and cycle time reduced to 2 hourly when fluid overload is evident. Once the patient is euvolemic, the dextrose concentration and cycle time should be adjusted to ensure a neutral fluid balance(1C) . (4.4) Where resources permit, creatinine, urea, potassium and bicarbonate levels should be measured daily; 24 h K t / V urea and creatinine clearance measurement is recommended to assess adequacy when clinically indicated(practice point) . (4.5) Interruption of dialysis should be considered once the patient is passing >1 L of urine/24 h and there is a spontaneous reduction in creatinine(practice point) . : The use of peritoneal dialysis (PD) to treat patients with acute kidney injury (AKI) has become more popular among clinicians following evidence of similar outcomes when compared with other extracorporeal therapies. Although it has been extensively used in low-resource environments for many years, there is now a renewed interest in the use of PD to manage patients with AKI (including patients in intensive care units) in higher income countries. Here we present the update of the International Society for Peritoneal Dialysis guidelines for PD in AKI. These guidelines extensively review the available literature and present updated recommendations regarding peritoneal access, dialysis solutions and prescription of dialysis with revised targets of solute clearance.